Clinicopathological Characteristics of Hepatocellular Carcinoma at a Tertiary Hospital: A Retrospective Study - Rum Affida Rasfa; Noza Hilbertina; Aswiyanti Asri; Yenita -; Loli Devianti (The Indonesian Society for Digestive Endoscopy, 2026)
Background: Hepatocellular carcinoma (HCC) is the sixth most common cancer globally and shows significant regional variations in clinicopathological characteristics. Limited data exist on HCC patterns in Indonesia, particularly in West Sumatra. This study aimed to characterize the clinicopathological features of HCC at Dr. M. Djamil Hospital, Padang, from 2021to2024.Methods: A descriptive retrospective study was conducted using medical records and histopathological re-evaluation of 46 HCC cases. Specimens were examined for demographic data, tumor characteristics, histopathological subtypes according to the WHO 2019 classification, differentiation grade, lymphovascular invasion, and background liver pathology.Results: The median age was 56 years, with male predominance (60.9%). Most specimens were resection specimens (60.9%) with tumor size ≥4 cm in 47.8% of cases and single nodules in 52.1%. Clear cell (39.1%) and macrotrabecular massive (37.0%) were the predominant subtypes, contrasting with global data showing NOS predominance. Most tumors were moderately differentiated (63.0%), with lymphovascular invasion present in 65.2% and cirrhotic background in 58.7% of casesConclusion: HCC in West Sumatra demonstrates distinct histopathological patterns, with a predominance of clear cell and macrotrabecular massive subtypes and high rates of lymphovascular invasion. These finding suggest histopathological features associated with aggressive tumor behavior (particularly macrotrabecular massive subtype and lymphovascular invasion), although no clinical outcome or survival analysis was performed.